2020
DOI: 10.22495/rgcv10i3p4
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy shocks and stock market volatility in emerging markets

Abstract: This paper examines the effect of monetary policy decisions on stock markets in emerging economies particularly South Africa for the period 2000Q1 to 2016Q4. This is important as the monetary authorities would understand how their decisions may cause reactions to the stock market. Monetary policy directly shocks money supply and repo rate and indirectly GDP and inflation among many macroeconomic variables. A hypothesis that stock markets do not respond to monetary policy determinations is formulated and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Indeed, regulations constitute frictions that distort buying and selling at the exchange (Olbrys & Majewska, 2014). This finding tends to support Zare et al (2013) that monetary policy (Interest rate in their study) influences stock market volatility; as well as Tchereni and Mpini (2020) who reveal that repo rate (the equivalent of the monetary policy rate in Nigeria) has a positive impact on volatility.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Indeed, regulations constitute frictions that distort buying and selling at the exchange (Olbrys & Majewska, 2014). This finding tends to support Zare et al (2013) that monetary policy (Interest rate in their study) influences stock market volatility; as well as Tchereni and Mpini (2020) who reveal that repo rate (the equivalent of the monetary policy rate in Nigeria) has a positive impact on volatility.…”
Section: Resultssupporting
confidence: 52%
“…The result revealed that policy on deposit reserve ratio influences stock market volatility. Tchereni and Mpini (2020) considered the impact of monetary policy on stock market volatility in South Africa for the period spanning the first quarter of 2000 to the fourth quarter of 2016, applying an error correction model. Results revealed that the money supply negatively influences volatility, while the repo rate has a positive effect on volatility.…”
Section: Theoretical Foundation For the Studymentioning
confidence: 99%
“…The final test of the studies (eg. Bissoon et al, 2016;Sahu and Pandey, 2020;Zhang and Zheng, 2020;Tchereni and Mpini, 2020). These results also explain that monetary policy is also effective for emerging market stock markets.…”
Section: Discussionmentioning
confidence: 58%
“…A. Khan, Ejaz, and Safdar (2023) Khan and Ejaz (2023) tested and discussed monetary freedom related supportive policies (like financial freedom, investment freedom, and trade freedom, government transparency, judicial effectiveness and rule of law) with stable politics and foreign exchange rate pose a positive and significant correlation with the equity market development (Ali, Javid, Ahmad, Ahmad, & Khan, 2021;Suhaibu, Harvey, & Amidu, 2017;Tchereni & Mpini, 2020).…”
Section: Introductionmentioning
confidence: 99%